Examining the relationship between employees’ perceptions on competency training and affective commitment: The moderating influence of volition - Happy, F.; Lew, Tek Yew; Sim, Adriel (INSInet Publications, 2013)
The purpose of this study is to examine the relationship between employees’ perceptions on competency training and affective commitment and the moderating effect of employees’ volition on this relationship. Data were collected from a field survey of 159 technicians from selected institutes in Sarawak. Regression analysis indicated that there was a positive relationship between employee’s perceived training comprehensiveness and affective commitment. In addition, the results indicated that the relationship between employee’s perceptions on competency training and affective commitment will be more positive for those who take on the competency training by own volition. Implications for researchers and practitioners are proposed based on the findings.